2011
DOI: 10.1002/cphc.201000889
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer between Genetically Modified Hansenula polymorpha Yeast Cells and Electrode Surfaces via Os-complex modified Redox Polymers

Abstract: Graphite electrodes modified with redox-polymer-entrapped yeast cells were investigated with respect to possible electron-transfer pathways between cytosolic redox enzymes and the electrode surface. Either wild-type or genetically modified Hansenula polymorpha yeast cells over-expressing flavocytochrome b2 (FC b(2) ) were integrated into Os-complex modified electrodeposition polymers. Upon increasing the L-lactate concentration, an increase in the current was only detected in the case of the genetically modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…This would mean that the electron exit via the photosynthetic redox complexes (PRCs) of prokaryotic cyanobacteria should in principle be comparatively easier than those of their eukaryotic counterparts. Os-polymers supply the systems including bacterial cells, [17][18][19] with high concentrations of stable mediating functionalities; form a 3D hydrogel [ 20 ] containing multiple layers of enzymes/ cells, [ 21 ] in which substrates and products can easily diffuse in and out. However, the inevitability of regular and continuous addition of these mediators makes them technologically unfeasible, environmentally unfriendly, practically incompatible [ 6 ] and maybe harmful for cells.…”
mentioning
confidence: 99%
“…This would mean that the electron exit via the photosynthetic redox complexes (PRCs) of prokaryotic cyanobacteria should in principle be comparatively easier than those of their eukaryotic counterparts. Os-polymers supply the systems including bacterial cells, [17][18][19] with high concentrations of stable mediating functionalities; form a 3D hydrogel [ 20 ] containing multiple layers of enzymes/ cells, [ 21 ] in which substrates and products can easily diffuse in and out. However, the inevitability of regular and continuous addition of these mediators makes them technologically unfeasible, environmentally unfriendly, practically incompatible [ 6 ] and maybe harmful for cells.…”
mentioning
confidence: 99%
“…Several yeast strains have been studied as biocatalysts in MFC with or without external mediator such as Saccharomyces cerevisiae (S. cerevisiae) [41][42][43][44][45][46][47][48][49][50][51][52], Candida melibiosica 2491 (C. melibiosica) [53][54][55][56], Hansenula anomala (H. anomala) [40], Hansenula polymorpha (Hansenula polymorpha) [57], Arxula adeninivorans (A. adeninivorans) [58] and Kluyveromyces marxianus (K. marxianus) [59].…”
Section: Yeast As a Biocatalyst In Mfcsmentioning
confidence: 99%
“…The electron transfer pathways between the cytosolic redox enzymes of H. polymorpha, overexpressing flavocytochrome b2 (FC b2), and the electrode surface was studied [57]. Both wild and genetic H. polymorpha yeast cells were entrapped in osmium-complex-modified redox polymers (OsRP), which are essential for the electron transfer communication, on the surface of graphite electrodes.…”
Section: H Polymorphamentioning
confidence: 99%
“…The idea of employing yeasts as a substitute to bacteria in BESs is surfacing, since they are robust and generally nonpathogenic. With regard to their capability to metabolize a wide range of substrates and high growth rates, Shkil et al [45] reported the electrochemical communication of Hansenula polymorpha with a graphite electrode, by wiring with osmium redox systems V, VI and VII. Here, genetically modified yeast cells that overexpress FCb2 (flavocytochrome b 2 ) generated more significant current with the aid of these osmium redox systems compared with that observed for the wild-type cells, highlighting that a plasma membrane redox system (FCb2) is crucial for ET.…”
Section: Wiring Of Microbial Cells To the Electrode Via Osmium Redox mentioning
confidence: 99%
“…Based on [44]. (B and C) Exemplary schemes that show electrical wiring of Gram-positive bacterial cell [43] and yeast cell [45] respectively to the electrode via osmium complexes.…”
Section: Wiring Of Microbial Cells To the Electrode Via Osmium Redox mentioning
confidence: 99%